IMPLEMENTASI APLIKASI MULTIMEDIA DAN PENGOLAHAN DATA LAYANAN PADA KANTOR URUSAN AGAMA KECAMATAN PASAR JAMBI - Kahar, Novhirtamely; Nisa, Khoirotun; -, Tamrinsyah (JURNAL AKADEMIKA, 2024)
Pasar Jambi District Religious Affairs Office, Jambi City, Jambi Province. The function of the Pasar Jambi District Religious Affairs Office is to carry out marriage registration, reconciliation, mosque construction, zakat, endowments and other social services. This research is to build a Multimedia Application Service for the Pasar Jambi District Religious Affairs Office. The Service Multimedia Application is a comprehensive overview of marriage registration which includes information, registration, announcements, services, facilities and infrastructure as a back-up for the Pasar District KUA Service Multimedia Application. Therefore, profile and service data must be available, complete and accountable. Through thesis activities, Nurdin Hamzah University tried to create a multimedia service application at KUA Pasar which is located in Jambi Province in an effort to create a Multimedia Application for Wedding Services at KUA Pasar Jambi. Based on the identification of the problem, therefore, the objectives of this thesis research activity are: 1) create a profile of the KUA Pasar and 2) a Multimedia Application for Wedding Services that can be accessed computerized and programmed using the Visual Studio Code programming language, MySQL database, XAMPP, Capcut and Medibang Paint. The requirements for the KUA Service Multimedia Application System are: 1) The input required in creating the system is service video data, 2) The processes required for creating the system are the main page process, the history page process, the structure page process, and the vision and mission page process and 3) The output required is a video of KUA services.